2019
DOI: 10.1007/s12471-019-01323-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tailored telemonitoring on functional status and health-related quality of life in patients with heart failure

Abstract: BackgroundFunctional status and health-related quality of life (HRQoL) are important in patients with heart failure (HF). Little is known about the effect of telemonitoring on functional status and HRQoL in that population.Methods and resultsA total of 382 patients with HF (New York Heart Association class 2–4) were included in a randomised controlled trial to investigate the effect of tailored telemonitoring on improving HRQoL and functional status in HF patients. Randomisation was computer-generated with str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…We identified 31 studies that compared structured telephone support with usual care, which included a total of 11,270 patients [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The study characteristics, as well as the reported outcomes on all-cause mortality, all-cause hospitalization, and HF-related hospitalization rates of the five largest studies, representing 49% (5560) of all patients, will be discussed in detail below [ 19 , 21 , 22 , 23 , 34 ].…”
Section: Structured Telephone Support Versus Usual Carementioning
confidence: 99%
See 2 more Smart Citations
“…We identified 31 studies that compared structured telephone support with usual care, which included a total of 11,270 patients [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The study characteristics, as well as the reported outcomes on all-cause mortality, all-cause hospitalization, and HF-related hospitalization rates of the five largest studies, representing 49% (5560) of all patients, will be discussed in detail below [ 19 , 21 , 22 , 23 , 34 ].…”
Section: Structured Telephone Support Versus Usual Carementioning
confidence: 99%
“…The quality of life of patients who received structured telephone support improved significantly more than standard care in seven studies [ 19 , 21 , 22 , 26 , 28 , 41 , 45 ], and non-significantly in one study [ 27 ]. In contrast, five studies did not show a larger improvement in the quality of life [ 15 , 16 , 29 , 30 , 46 ].…”
Section: Structured Telephone Support Versus Usual Carementioning
confidence: 99%
See 1 more Smart Citation
“…Telemonitorování tedy dle této studie může pomoci zabránit zhoršení pohybové kapacity u této skupiny pacientů. 14 Podle odborného stanoviska expertů Asociace srdečního selhání Evropské kardiologické společnosti a jejich shrnutí nových poznatků v léčbě i péči o pacienty se srdečním selháním z roku 2019 může být telemedicína u těchto pacientů zvážena především s cílem snížit riziko rehospitalizací a úmrtí z kardiovaskulárních příčin. Dle dostupných vědeckých poznatků studie TIM-HF2 bylo prokázáno snížení rizika neplánované rehospitalizace a úmrtí díky dálkové monitoraci, která zahrnovala domácí měření hmotnosti, EKG, krevního tlaku a hodnocení zdravotního stavu ve strukturovaném systému s nepřetržitou podporou a dostupností lékaře a s úpravou léčby podle získaných údajů.…”
Section: Moderní Technologie V Péči O Pacientyunclassified
“…However, existing results are mixed regarding effects of home telemonitoring applications on HRQoL in elderly people with chronic diseases. Results from randomized controlled trials (RCTs) with elderly multimorbid people using a telemonitoring system showed improvements in HRQoL in study participants [19][20][21][22], although other telemonitoring RCTs could not achieve congruent results [23][24][25][26]. There is also evidence that the effects of telemonitoring on those with mental disorders, such as depression and mild cognitive impairment (MCI), can be promising [27][28][29].…”
Section: Introductionmentioning
confidence: 99%